Hoarding Disorder Trough Three Case, A New Mental Disorder in DSM-5 - Süheyla DODAN BULUT; Esra ALATAS; Tonguç BERKOL; Halime Şeyma ÖZCELIK; Serdar BULUT (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Compulsive hoarding is a problem characterized with excessive collection and accumulation, failure to discard the excess amount of collected items. Although it is considered to be a symptom of obsessive-compulsive disorder in DSMIV- TR (Diagnostic and statistical manual of mental disorders fourth edition text revision), it is thought that compulsive hoarding and OCD may have different biological, cognitive and behavioral mechanisms and compulsive hoarding may be associated with many other psychological illnesses. For these reasons, in DSM-5 (Diagnostic and statistical manual of mental disorders fifth edition) hoarding disorder diagnosis is located under the classification of obsessive-compulsive and related disorders. In this case report, three cases classified in different diagnostic categories according to DSM-IV-TR will be mentioned and hoarding disorder will be discussed.